ABCB4 Gene Aberrations in Human Liver Disease: An Evolving Spectrum - Reichert, Matthias Christian; Lammert, Frank (Seminars in Liver Disease, 2018)
ATP-binding cassette subfamily B member 4 (ABCB4) is a phospholipid translocator at the canalicular membrane of the hepatocyte, which “flops” phosphatidylcholine into bile. Dysfunction of this transporter due to ABCB4 gene variants can cause liver diseases and has been called ABCB4 deficiency. Several diseases including progressive familial intrahepatic cholestasis type 3 (PFIC3), low phospholipid-associated cholelithiasis (LPAC), a subgroup of patients developing intrahepatic cholestasis of pregnancy (ICP), drug-induced liver injury and chronic cholangiopathy with biliary fibrosis and cirrhosis were attributed to ABCB4 deficiency and characterized in the past decade. LPAC and ICP are usually caused by monoallelic variants, whereas patients affected by PFIC3 are homozygous or compound heterozygous carriers of ABCB4 variants. Treatment with ursodeoxycholic acid is often effective, but as the more severe forms of ABCB4 deficiency progress, nevertheless, new diagnostic and therapeutic approaches are warranted. Current functional classifications for ABCB4 deficiency–associated mutations can guide the development of novel genotype–based targeted pharmacotherapies for these conditions. Recently, increasing evidence from genome-wide association studies is emerging on associations of ABCB4 variants with hepatobiliary malignancies.
Keywords: ABC transporter B4; bile acids; cholestasis; phospholipids; phosphatidylcholine translocator